Uranium and thorium partitioning in the bulk silicate Earth and the oxygen content of Earth's core. (15th April 2020) - Faure, P.; Bouhifd, M.A.; Boyet, M.; Manthilake, G.; Clesi, V.; Devidal, J.-L.
Abstract: This study investigates the partitioning of U and Th between molten metal and silicate liquid ( D U and D Th ) during Earth's core-mantle differentiation. We report new Th partition coefficients between chondritic silicate melt and various Fe-rich alloys in the system Fe-Ni-C-S-Si as determined by experiments in a multi-anvil apparatus at 3–8 GPa, 2073–2373 K, and oxygen fugacities from 1.5 to 5 log units below the iron-wüstite (IW) buffer. By compiling all existing data on molten metal-silicate liquid partitioning of U and Th, we develop global models of U and Th partitioning between the mantle and core throughout Earth's accretion. The calculated concentrations in the Bulk Silicate Earth (BSE) are in agreement with previous studies (UBSE  = 11.42 ± 0.45 ppb and ThBSE  = 43.20 ± 1.73 ppb), whereas the contents of these radioactive elements in the Earth's core remain negligible. Compared to recent geochemical estimations, the calculated (Th/U)BSE supports EL rather than EH enstatite chondrites as the reduced building blocks of the Earth. Furthermore, we demonstrate that Th is much more sensitive than U to the oxygen content of the metallic phase. To reproduce the Th/U ratio of the BSE within its uncertainties, the oxygen content of the Earth's core must be lower than 4.0 wt%. By combining other existing constraints, this suggests that the core contains 2.0–4.0 wt% O. The calculations of U and Th concentrations and Th/U in the BSE developed herein can be used as new constraints for determining the concentrations of other refractory lithophile elements in the BSE as soon as their metal-silicate partition coefficients are well constrained over the conditions of core segregation.